2008
DOI: 10.2176/nmc.48.474
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Epidural Pneumocephalus -Case Report-

Abstract: A 20-year-old male presented with an extremely rare spontaneous epidural pneumocephalus which was successfully treated by a single neurosurgical intervention. The patient had a habit of nose blowing and a 1-year history of progressive headache and nausea. Cranial computed tomography (CT) revealed a 2 × 7 cm right temporo-occipital epidural pneumocephalus with extensive hyperpneumatization of the mastoid cells. Right temporo-occipital craniotomy with a right superficial temporal artery and vein flap repair resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 21 publications
0
25
0
2
Order By: Relevance
“…The first case report of pneumocephalus was in 1741 by Lecat. (1,26) Its association with craniofacial trauma, neurosurgical or ontological procedures, (9,14,23,24) otomastoiditis,(5) or skull base tumours (21,27) is well known. Spontaneous pneumocephalus caused by a primary defect at the temporal bone level without association with pathological conditions or surgery is very rare.…”
Section: Discussionmentioning
confidence: 99%
“…The first case report of pneumocephalus was in 1741 by Lecat. (1,26) Its association with craniofacial trauma, neurosurgical or ontological procedures, (9,14,23,24) otomastoiditis,(5) or skull base tumours (21,27) is well known. Spontaneous pneumocephalus caused by a primary defect at the temporal bone level without association with pathological conditions or surgery is very rare.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a history of infection favors the congenital theory of a hyperpneumatized mastoid, with either an excessive bone resorption during pneumatization or faulty embryogenesis. An additional role of the eustachian tube functioning as a oneway valve may help to increase the air pressure [13][14][15]. (3) Spontaneous pneumocephalus can be caused by barotraumas, but this is extremely rare [14].…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous pneumocephalus has also been described. 15,17,32,46,50,52 Initially reported on by Lecat in 1741, 16,49 the mechanism of pneumocephalus was further examined in 1884 by Chiari, who advanced the hypothesis of a fistular tract between paranasal sinuses and the cranial cavity. 34 In 1913, Luckett used plain skull radiographs to detect a traumatic pneumocephalus.…”
Section: Postoperative Pneumocephalusmentioning
confidence: 99%
“…24,27,40,41 Some authors have reported a 100% incidence of pneumocephalus if imaging is done within the first 2 days of supratentorial craniotomy. 50 Clearly, the timing and resolution of the imaging technique will alter pneumocephalus rates as air is progressively absorbed after surgery. There is little information on rates of pneumocephalus following ESBS.…”
Section: Postoperative Pneumocephalusmentioning
confidence: 99%